2004
DOI: 10.1063/1.1699505
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopic study of the site occupancy distribution of cations in nickel cobalt oxides

Abstract: Mid-infrared, far-infrared, and Raman spectra for Ni1−xCoxOy indicated the systematic variation from a spinel-type (x=1.0) to an inverse spinel-type (x=0.67) lattice, through a multiphase transition region, to an NaCl-type (x<0.25) structure. Further analysis reveals that a decrease in x in this system is accompanied by the formation of octahedral/Ni2+, which, in the case of spinel compositions Ni1−xCoxO4/3 (x=0.67 to 1.0), results in substitution of Co3+ into tetrahedral sites and/or the redistribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 23 publications
2
47
0
1
Order By: Relevance
“…This is similar to the observations which Windisch et al 44 replacement of Co 3+ by Ni 2+ ions and the decrease in peak intensity and increase of bandwidth with the related decrease of symmetry at the O h site. 44 In order to demonstrate the presence of weak Raman peaks in the stoichiometric (Co 1−x Ni x ) 3 O 4 films with x=0.33, an inset with the Raman spectrum of a thicker film (∼ 192 nm) is included in Figure 5. Iliev et al 42 also observed weak and broad peaks for their metallic films grown at low temperatures but obtained sharp peaks for their insulating films grown at high temperatures during their epitaxy studies supporting the idea that ionic disorder is responsible for the low resistivity.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This is similar to the observations which Windisch et al 44 replacement of Co 3+ by Ni 2+ ions and the decrease in peak intensity and increase of bandwidth with the related decrease of symmetry at the O h site. 44 In order to demonstrate the presence of weak Raman peaks in the stoichiometric (Co 1−x Ni x ) 3 O 4 films with x=0.33, an inset with the Raman spectrum of a thicker film (∼ 192 nm) is included in Figure 5. Iliev et al 42 also observed weak and broad peaks for their metallic films grown at low temperatures but obtained sharp peaks for their insulating films grown at high temperatures during their epitaxy studies supporting the idea that ionic disorder is responsible for the low resistivity.…”
Section: Resultssupporting
confidence: 80%
“…Bitla et al 19 who investigated similar films (epitaxial, on MgAl 2 O 4 ) carried out extensive investigations of the cation distribution by X-ray absorption spectroscopy (XAS) and obtained (Co 43 Another F 2g would be expected at about 522 cm −1 but cannot be identified here due to the interference with a signal from Si. When Ni is added, the intensity of the peaks decreases dramatically, its width increases and the A 1g peak that is usually assumed to be dominated by the O h oxygen atoms 44 shifts to lower wavenumbers. This is similar to the observations which Windisch et al 44 replacement of Co 3+ by Ni 2+ ions and the decrease in peak intensity and increase of bandwidth with the related decrease of symmetry at the O h site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2a The Raman band at 658 cm −1 is a shoulder peak and it shows the same A 1g symmetry which also can be assigned to the peak at 682 cm −1 , and both the peaks arise due to the vibrational energy from stretching of Co-O bonds. All these peaks are characteristic peaks for a normal spinel like ZCO and other spinels that are more or less similar to ZCO [55][56][57][58][59]. The characteristic 'D' and 'G' bands at 1345 and 1585 cm −1 , respectively, clearly depict the presence of RGO [60].…”
Section: Resultsmentioning
confidence: 97%
“…It could be successfully explained in terms of resonant anharmonic interaction of the high-E 2 mode with a band of combined transverse and longitudinal acoustic modes, as the steep variation of the 2-phonon density of states around the high-E 2 frequency leads to a distorted phonon line shape. One can suggest that mixing 2 different cations through doping in aqueous solution could affect the local polarizability by charge distribution and result in at least 1 vibrational mode being strongly influenced [6,19,20].…”
Section: Experimental Details On Hydrothermal Growth Of Doped Zno Nanmentioning
confidence: 99%